METADISCOURSE MARKERS IN INTRODUCTION SECTION OF MASTER THESES IN ENGLISH EDUCATION STUDY PROGRAM STUDENTS AT UNIVERSITY OF BENGKULU - Neris Mayang Ledy; Syafryadin Syafryadin; Iis Sujarwati (Universitas Wiralodra, 2024)
Metadiscourse refers to the language elements that writers or speakers use to organize, guide, and comment on their text, helping readers understand the structure and connect ideas. This study investigates the critical role of metadiscourse markers in the introduction sections of master's theses, focusing on how these markers enhance clarity and organization, making the text more accessible and engaging. The research aimed to analyze the types and frequencies of both interactive and interactional metadiscourse markers in the introductions of theses by students in the English Education Study Program at Bengkulu University. A mixed-methods approach was employed to analyze 30 introduction sections. The findings show that writers predominantly use interactive markers, especially transitions (70.7%), evidentials (11.7%), and frame markers (8.3%), more than interactional markers like hedges (52.2%) and engagement markers (24.8%). The frequent use of transition markers suggests a focus on guiding readers through the text rather than direct engagement. These results underscore the importance of metadiscourse markers in creating a well-structured and persuasive introduction. Mastering these markers can significantly enhance the quality of academic writing. Future research could extend this analysis to other thesis sections or different academic contexts.